2005
DOI: 10.1177/0013124505279959
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture and Academic Achievement in Secondary Schools

Abstract: A number of factors have been identified that affect academic achievement of learners. Among these factors, organizational culture seems to be a key factor. This is a complex factor characterized by many variables. To classify the variables included in organizational culture, a theoretical model was constructed. Two sets of variables were identified from the model: the tangible and intangible variables. The findings in this research indicate that a healthy and positive organizational culture exists in high-ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 7 publications
1
16
0
1
Order By: Relevance
“…Findings from organisational culture research (Ridder, 2004;Westhuizen, Mosoge, Swanepoel, & Coetsee, 2005) indicate that a healthy and positive organisational culture exists in high-achieving schools; the same cannot be said for low achieving schools. Hart's (1992) 'Ladder of Children's Participation' and Shier's 'Pathways to Participation' (2001) are commonly used in discussion of young people's participation.…”
Section: R Sharpmentioning
confidence: 99%
“…Findings from organisational culture research (Ridder, 2004;Westhuizen, Mosoge, Swanepoel, & Coetsee, 2005) indicate that a healthy and positive organisational culture exists in high-achieving schools; the same cannot be said for low achieving schools. Hart's (1992) 'Ladder of Children's Participation' and Shier's 'Pathways to Participation' (2001) are commonly used in discussion of young people's participation.…”
Section: R Sharpmentioning
confidence: 99%
“…Z existujúcich štúdií vyplýva, že efektívna organizačná kultúra súvisí s vyššou motiváciu vzdelávať sa (učitelia) a učiť sa (žiaci) a prejavuje sa v celkových výsledkoch školy [Van der Westhuizen et al 2005]. Zistilo sa tiež, že efektívna organizačná kultúra zvyčajne vedie k zníženiu počtu žiakov, ktorí odchádzajú zo školy, ako aj k zníženiu ich neúspechov v oblasti vzdelávania.…”
Section: Vplyv Kultúry šKoly Na Jej Výsledkyunclassified
“…(2005) and Stewart i20(lX) indicate that school cullure cv(.>Kes a set of unv\ritten beliefs, norms, values, attitudes, and various forms of interaction among pupils, teachers and administrators. Organizational eulture also displays the unique character of each school and exercises a specific inllucnce on ihc behaviotir oi'schooi members (Van der Westhuizen et al 2005). Furthermore, sehooi eulture ean also affect the pupils' sense of belonging the extent to vvhieh pupils feel accepted, respeeted and supported in schools-Research has shown that the pupils" sense of belonging niHuenees their academic achievement (Ma 2003).…”
Section: (K)4) Stewart (2{)i)s)mentioning
confidence: 99%
“…i-mpu"iea! research eoniirms that sehools that are performing welt or average have a strong and effeetive organizational culture, whereas poorly performing sehools have a weak and even negative organizational culture ( Van der Westhuizen et al 2005). To improve academic achievement, it is crticial to pay attention to the school'^ organizational cuUure and especially to work to improve It in low performing schools.…”
Section: (K)4) Stewart (2{)i)s)mentioning
confidence: 99%